Pelvic Inflammatory Disease Caused by Salmonella Bacteremia: Report of Two Cases - Özdeğirmenci, Özlem; Kayıkçıoğlu, Fulya; Aksu, Gönül; Güneş, Muzeyyen; Haberal, Ali (Gynecology Obstetrics & Reproductive Medicine, 2011)
Pelvic inflammatory disease (PID) is one of the most serious complications of the sexually transmitted diseases. The most important step in early diagnosis is a high index of clinical suspicion. In this report, we document two cases of PID due to Salmonella bacteremia.